Grevillea robusta A. Cunn. (Proteaceae) initial growth in substrates with urban domestic waste compost - Grolli, Paulo Roberto; Kãmpf, Atelene Normann (Pesquisa Agropecuaria Brasileira, 1994)
This work aimed to evaluate the effects of urban domestic waste compost (UWC) mixed with mineral soil (MS) or organic soil (peat) (P) on Grevillea robusta production. The experiment was arranged in a complete randomized block design. The six treatments consist of a mixture of these materials in different proportions: 1MS:1P; 1UWC:1MS; 1UWC:2MS; 1UWC:1P; 1UWC:2P and 1UWC:1MS:1P. Physical and chemical characteristics of the substrates and the effects of these characteristics on plant growth were evaluated. The 1UWC:2P treatment determined a better shoot growth, with an increase in dry weight, plant height and leaf number. There was no significant difference among treatments on the root growth. The plant growth showed the possibility of the use of the urban domestic waste compost as a conditionant factor for horticultural substrates preparation for plant production in nursery.